EVOLUTION AND OPTIMIZATION OF MUSTARD CULTIVATION IN HARYANA: A COMPREHENSIVE STUDY - Priyanka; Kiran Bala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Haryana, located in northern India, cultivates a diverse range of crops due to its fertile soil, favorable climate, and well-developed irrigation infrastructure. This research paper presents a comprehensive analysis of mustard cultivation in Haryana, India, from 1966 to 2021, examining the trends in area under cultivation, production output, and yield efficiency. Utilizing historical data, the study identifies significant growth patterns, evaluates the impact of agricultural practices, and explores the role of technological advancements and policy interventions in shaping the mustard cultivation landscape in the region. By analyzing district-level variations, the paper sheds light on the heterogeneous nature of agricultural development across Haryana. The research employs statistical methods to forecast future trends and offers recommendations for sustainable cultivation practices to enhance productivity, profitability, and environmental sustainability in mustard farming.